Musadoc 2006 - International Network for the Improvement of Banana and Plantain (2007)
Includes updated versions of the databases MUSALIT - which contains over 10.000 bibliographic records and abstracts on Musa - and BRIS - a database of almost 900 records on banana researchers. MusaDoc 2006 also includes the most recent publications: latest issues of InfoMusa, proceedings, strategy papers and technical manuals as well as the INIBAP Annual reports 2004 and 2005. The CD-Rom also provides an updated summary of our activities.